Analysis Financial Distress Potential in Asean Industrial Companies Using Altman Z-Score and Springate Methods - Resmi Yunisa; Fitri Santi (East Asian Journal of Multidisciplinary Research, 2023)
This research aims to analyze the potential for financial distress in the industrial sector companies across five ASEAN countries, using the Altman Z-score (1993) and Springate (1978) methods. Subsequently, these estimations are utilized to determine the error rate in classifying companies into specific groups, such as failed, safe, and grey-area companies. To measure the significance of differences among these groups, an independent sample t-test is employed. The bankruptcy analysis results from the Altman Z-Score and Springate methods within the industrial sector companies across ASEAN countries (Indonesia, Malaysia, Philippines, Singapore, and Thailand) in 2018 until 2020 indicate varying levels of financial distress.